"Verrucario viridulae-Staurotheletum hymenogoniae", a new calcicolous lichen community as a component of petrophytic grassland habitats in the Northern Black Sea region - Khodosovtsev, Alexander Ye.; Darmostuk, Valeriy V.; Didukh, Yakiv P.; Pylypenko, Igor O. (Mediterranean Botany, 2019)
The new lichen association, Verrucario viridulae-Staurotheletum hymenogoniae (Aspicilion contortae Roux 2009, Aspicilietalia calcareae Roux 2009, Verrucarietea nigrescentis Wirth 1980) is described here. It is formed on marl limestone pebbles in arid landscapes in the Northern Black Sea lowland. Forty-six species of lichens and ten lichenicolous fungi were observed and Staurothele hymenogonia, Verrucaria muralis s. lat., V. viridula are diagnostic for the association. The new association is a component of the Nord-Pontic calcicline pale fescue grasslands habitats (EUNIS). It occurs in protected areas “Yelanetsky Steppe” (Mykolayiv region), “Troitska balka” (Zaporizha region), the National Nature Park “Kam`yanska Sich” and the Regional Landscape Park “Gavrylovsky” (Kherson region).